On some generalization of Favard theorem for multidimensional case - Vizel, Ya. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Я. Ф. Визель. Об одном обобщении теоремы Фавара на многомерный случайJ. Vizelis. Apie vieną Favaro teoremos apibendrinimą daugiamačiui atvejui